2011
DOI: 10.4137/cgm.s7113
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Vascular Endothelial Growth Factor Levels as a Prognostic Marker for Stage II or III Colorectal Cancer Patients

Abstract: Background:The aim of the present study was to determine whether serum vascular endothelial growth factor (VEGF) can provide prognostic information independent of carcinoembryonic antigen levels in patients undergoing curative surgery. Methods: Serum samples were collected from 158 patients with colorectal cancer and from 100 controls. Serum and tissue levels of VEGF were measured by enzyme-linked immunosorbent assay. Serum VEGF levels in colorectal cancer patients were compared with those in healthy controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…However, the study in laryngeal cancer by Lv et al (2011) found that serum VEGF-A level was elevated in advanced T-stage patients (T3-4) in comparison to early T-stage (T1-2); and it was also elevated in patients with metastatic disease in comparison to non-metastatic disease. Similar study by Kemik et al (2011) in colorectal cancer, observed significantly higher level of serum VEGF-A in (T3-4) vs early T-stage (T1-2); and it was also elevated in patients with metastatic disease as compared to non-metastatic disease. This conflicting result shows necessity of further evaluation of Serum VEGF-A level in large cohort of patients.…”
Section: Serum Vegf-a Level and Treatment Responsesupporting
confidence: 67%
“…However, the study in laryngeal cancer by Lv et al (2011) found that serum VEGF-A level was elevated in advanced T-stage patients (T3-4) in comparison to early T-stage (T1-2); and it was also elevated in patients with metastatic disease in comparison to non-metastatic disease. Similar study by Kemik et al (2011) in colorectal cancer, observed significantly higher level of serum VEGF-A in (T3-4) vs early T-stage (T1-2); and it was also elevated in patients with metastatic disease as compared to non-metastatic disease. This conflicting result shows necessity of further evaluation of Serum VEGF-A level in large cohort of patients.…”
Section: Serum Vegf-a Level and Treatment Responsesupporting
confidence: 67%
“…Several clinical trials in CRC patients indicate an inverse relationship between the concentration of VEGF-A in serum or tumor tissue and the clinical outcome [ 9 11 ]. Furthermore, certain VEGF-A polymorphisms have been associated with altered VEGF-A production or promoter activity, causing variability in response to treatment [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that serum VEGF is an independent prognostic factor [63][64][65][66]. It has been shown [67] that increased preoperative circulating VEGF levels cor-relate with factors reflecting disease progression including tumor size, and nodal and distant metastases in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%